Disposal practices of expired and unused medications among households in Mwanza, Tanzania - Marwa, Karol Julius (PLoS One, 2021)
BACKGROUND: The community practice towards disposal of expired and unused medications in spite of its adverse impact have been widely neglected in many developing countries. The available guidelines in Tanzania focus on the disposal of expired medications and cosmetics in hospitals and community pharmacies only. AIM: The aim of this study was to assess the disposal practice of expired and unused medications at household level in Mwanza city, north-western Tanzania. METHODOLOGY: The household based cross-sectional study was conducted among 359 randomly selected household members. Semi-structured questionnaires were used for interview during data collection and while STATA(®) version 13 was used for analysis. RESULTS: Out 359 households visited, 252 (70.19%) had medications kept in their houses at the time of data collection. Among them, 10 (4.0%) households had kept medications at their houses because they were still continuing with treatment while 242 (96.0%) kept unused medications which were supposed to be discarded. The main reason for keeping unused or expired medications at home was uncompleted course of treatment (199 (82.20%) after feeling that they had recovered from illness. The main reason for discarding medications were recovering from illness (141(48.7%) and expiry (136 (46.9%). The major discarding practices for medications were disposing into domestic trashes (219 (75.5%) and pit latrines (45 (15.5%). Majority of respondents (273 (76%) were aware that improper disposal of expired medications are detrimental to human health and environment in general. CONCLUSION: Improper disposal of unused and expired medications at household level was a common practice in the study area. Tailor-made interventions by the Food and Drugs Authority (FDA) and other national as well as local stake holders are urgently needed to address the situation.